Orchids - a shower of colours the 17th World Orchid Conference, 24 April - 2 May, 2002 - World Orchid Conference 2002 : [Shah Alam]); Malaysian Agricultural Research and Development Institute ([Kuala Lumpur] : MARDI, 2002)
Explains the varieties of orchids that comes from the research that made by MARDI
Keywords: Orchids -- Malaysia -- Congresses; Orchids -- Malaysia